2008
DOI: 10.1007/s00103-008-0646-y
|View full text |Cite
|
Sign up to set email alerts
|

Validierung von Sekundärdaten

Abstract: Medical records databases (such as the General Practice Research Database-GPRD) and administrative databases (such as German Statutory Health Insurance (SHI) claims data) are useful sources for pharmacoepidemiology and health services research. However, these data are not primarily collected for research purposes. Validation studies are needed to examine their completeness and accuracy depending on the corresponding research question. This article reviews strategies for checks of internal consistency within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 32 publications
2
14
0
10
Order By: Relevance
“…On the other hand, validity of diagnoses should be considered [40]. Although we studied newly diagnosed patients, we know that the coding of dementia diagnoses is made rather late due to taboo, stigmatization, difficulty in the diagnostic process, and poor therapeutic options [41-43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, validity of diagnoses should be considered [40]. Although we studied newly diagnosed patients, we know that the coding of dementia diagnoses is made rather late due to taboo, stigmatization, difficulty in the diagnostic process, and poor therapeutic options [41-43].…”
Section: Discussionmentioning
confidence: 99%
“…However, pain identification and management of pain should not be severely impaired by the absence of a precise etiological dementia diagnosis. In Germany, validation studies are scarce [40] and no data on the validity of the dementia diagnosis as well as of the types of pain are available.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported ICD-coding to be reliable on chapter level only and found relevant coding uncertainties at three- and four-digit coding level, too (kappa-values of approximately 0.4 and 0.2 for three-digit and four-digit coding, respectively) [24]. Until now, there have been few validation studies for routine data of German statutory health insurances [25]. That is why we can only estimate the true underlying number of children with each ICD 10 diagnosis as well as the true underlying number of children with pain or activity limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Größe, Gewicht, Laborparameter oder Tumorstadium) ist nicht vorhanden. Eine weitere Einschränkung betrifft die Validität dieser Daten, ein Aspekt, zu dem aus Deutschland bisher viel zu wenig bekannt ist [23]. Eine wichtige Voraussetzung, um Forschung praktikabel zu machen, ist die elektronische Erfassung der Daten.…”
Section: Routinedaten Der Krankenkassenunclassified